Exponential Attractor for a First-Order Dissipative Lattice Dynamical System - Xiaoming Fan (Journal of Applied Mathematics)
We construct an exponential attractor for a first-order dissipative lattice dynamical system arising from spatial discretization of reaction-diffusion equations in ℝ𝑘. And we obtain fractal dimension of the exponential attractor.